A Combination Adjuvant for the Induction of Potent Antiviral Immune Responses for a Recombinant SARS-CoV-2 Protein Vaccine - Jangra, Sonia; Landers, Jeffrey J.; Rathnasinghe, Raveen; O’Konek, Jessica J.; Janczak, Katarzyna W.; Cascalho, Marilia; Kennedy, Andrew A.; Tai, Andrew W.; Baker, James R.; Schotsaert, Michael; Wong, Pamela T. (Frontiers in Immunology, 2021)
Several SARS-CoV-2 vaccines have received EUAs, but many issues remain unresolved, including duration of conferred immunity and breadth of cross-protection. Adjuvants that enhance and shape adaptive immune responses that confer broad protection against SARS-CoV-2 variants will be pivotal for long-term protection. We developed an intranasal, rationally designed adjuvant integrating a nanoemulsion (NE) that activates TLRs and NLRP3 with an RNA agonist of RIG-I (IVT DI). The combination adjuvant with spike protein antigen elicited robust responses to SARS-CoV-2 in mice, with markedly enhanced TH1-biased cellular responses and high virus-neutralizing antibody titers towards both homologous SARS-CoV-2 and a variant harboring the N501Y mutation shared by B1.1.7, B.1.351 and P.1 variants. Furthermore, passive transfer of vaccination-induced antibodies protected naive mice against heterologous viral challenge. NE/IVT DI enables mucosal vaccination, and has the potential to improve the immune profile of a variety of SARS-CoV-2 vaccine candidates to provide effective cross-protection against future drift variants.